Indigenous Counseling Practices in Maintaining Stability of Marriage Based on Tradition of the Basemah Tribe's Pantauan Bunting - Hendar, Kus (Bulletin of Counseling and Psychotherapy, 2023)
This research aims to explore the practice of Indigenous Counseling in the context of Basemah ethnic marriages that follow the Pantauan Bunting cultural tradition in Pagaralam City, South Sumatra. The focus of the research is on how Indigenous Counseling is able to integrate traditional cultural values which have significance in the institution of marriage. The research method used is phenomenology with a field research approach, where researchers are directly involved in observations, interviews and documentation at the research location with 3 married couples as respondents. This research design includes a qualitative approach with triangulation data analysis techniques to ensure the validity and reliability of the findings. The results of this research reflect that Indigenous Counseling based on pantauan bunting is able to make a positive contribution to conflict resolution, increased communication, and deeper understanding between husband and wife couples. The abstract also includes an overview of the findings, highlighting the importance of cultural values in enriching counseling practice and providing a broader understanding of the success of Indigenous Counseling in supporting harmonious marital relationships.